Fetal magnetic resonance imaging in the diagnosis of spinal cord neural tube defects: A prospective study - Gao, Gan; Tao, Benzhang; Chen, Yanyan; Yang, Jiaqi; Sun, Mengchun; Wang, Hui; Hao, Fangbin; Liu, Simeng; Wang, Minjie; Shang, Aijia (Frontiers in Neurology, 2022)
Objective This study aimed to evaluate the value of fetal magnetic resonance imaging (MRI) in the prenatal diagnosis of spinal neural tube defects. Methods From August 2018 to January 2021, 56 fetuses with suspected spinal cord neural tube defects were treated by prenatal ultrasound in the Neurosurgery Department of the First Medical Center of the People's Liberation Army General Hospital. Fetal MRI was performed within 72 h after ultrasound diagnosis. Forty singleton fetuses were selected. Magnetic resonance examination was performed within 1 month after birth, and the diagnostic coincidence rates of prenatal ultrasound and fetal magnetic resonance examination in the prenatal diagnosis of spinal cord neural tube defects were compared and analyzed using postnatal magnetic resonance examination as the standard. Results The coincidence rates of prenatal ultrasound and fetal MRI for the prenatal diagnosis of spina bifida were 71.4% (20/28) and 39.2% (11/28), respectively, and the difference was statistically significant. The coincidence rates of prenatal ultrasound and fetal MRI in the diagnosis of intraspinal lipoma were 52.6% (10/19) and 73.7% (14/19), respectively, and the difference was statistically significant. Conclusion Fetal MRI has an advantage over prenatal ultrasound in detecting intraspinal lipoma. Prenatal ultrasound has an advantage over fetal MRI in detecting spina bifida.